Pengaruh Kombinasi Ekstrak Etanol Bawang Putih dan Kunyit terhadap Histopatologi Jantung dan Pankreas Tikus Diabetes - Ana Fiske Hotmaida Simanjuntak; Nerly Juli Pranita Simanjuntak; Razoki, Razoki (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Diabetes mellitus (DM) is a chronic condition characterized by increased blood glucose levels that require long-term treatment to maintain stable blood sugar levels. Garlic and turmeric rhizomes are known to contain secondary metabolite compounds that have the potential to lower blood glucose levels. This study aims to see how the combination of garlic and turmeric rhizome extracts affects the histopathological picture of the pancreas of male white rats (DM). This study uses an experimental design method with a designposttest only control group involving 30 white male rats divided into five groups: Negative control (K-), positive control (K+), and three treatment groups with extract doses of 100mg/kgBW (F1), 200mg/kgBW (F2), and 300mg/kgBW (F3). The results showed the most significant decrease in blood glucose levels in the 300mg/kgBW group (F3), namely (105mg/kgBW). The histopathological picture of the pancreas showed severe damage in group F1 (75% had necrosis), and moderate damage (50% with necrosis) in F2 and F3. The combination of garlic extract and turmeric rhizome has the potential to reduce blood glucose levels and improve the histopathological picture of the pancreas in DM rats.